Effectiveness of the Nutmeg Flower Dryer Monitoring Module in Improving Students’ Digital Literacy Comprehension - Andro Tuuk; Andrew Makaingate; Novlin Sadja; Leony Ariesta Wenno; Doostenreyk Niala kantohe (International Journal Labs, 2026)
The rapid advancement of technology has emphasized the need for digital literacy among vocational students, particularly in technology-intensive sectors. However, learning modules that effectively integrate vocational content with digital literacy skills remain limited. This study aimed to evaluate the effectiveness of a Nutmeg Flower Dryer Monitoring Module in improving students' digital literacy comprehension within a vocational education context. A quasi-experimental design with pretest-posttest control groups was employed, involving 60 eleventh-grade vocational students in electronics engineering programs. The experimental group (n=30) received instruction using the IoT-based monitoring module, while the control group (n=30) engaged in conventional textbook-based learning. Data were collected using a 40-item digital literacy test and a 20-item student response questionnaire, then analyzed through N-gain calculation and independent samples t-tests. Results revealed a significant improvement in the experimental group's digital literacy, with an overall N-gain of 0.71, categorized as highly effective. The greatest gains were observed in communication literacy, indicating enhanced competencies in interpreting and interacting with real-time digital systems. Students also reported high satisfaction and perceived relevance to vocational tasks. The findings confirm that contextualized, hands-on IoT modules effectively bridge theoretical knowledge and practical digital skills. Future work should explore multi-site implementation, longitudinal retention, and adaptation to other vocational domains to further optimize digital literacy outcomes.